2015
DOI: 10.1007/s00066-015-0884-5
|View full text |Cite
|
Sign up to set email alerts
|

Metformin influences progression in diabetic glioblastoma patients

Abstract: Corticosteroid therapy and hyperglycemia were strongly associated with impaired survival rates and serves as negative prognostic factors. Diabetes did not influence survival. Interestingly, our findings showed an association of metformin therapy and prolonged progression-free survival in glioblastoma patients with diabetes and therefore serve as a foundation for further preclinical and clinical investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 52 publications
3
45
0
Order By: Relevance
“…Although patients treated with sulfonylureas had worse outcomes, patients treated with metformin had higher median survival compared with all other anti-diabetic drugs (Welch and Grommes 2013). Two years later, Adeberg et al (2015) investigated the influence of diabetes mellitus, corticosteroid therapy and metformin therapy on progression and survival in primary GBM patients. Among 276 patients with primary GBM, forty patients (14.5 %) were identified with a pretherapeutic history of diabetes, and 20 (50 %) of them were treated with metformin (Adeberg et al 2015).…”
Section: Metformin Efficacy In Gbm: Clinical Evidencementioning
confidence: 99%
See 3 more Smart Citations
“…Although patients treated with sulfonylureas had worse outcomes, patients treated with metformin had higher median survival compared with all other anti-diabetic drugs (Welch and Grommes 2013). Two years later, Adeberg et al (2015) investigated the influence of diabetes mellitus, corticosteroid therapy and metformin therapy on progression and survival in primary GBM patients. Among 276 patients with primary GBM, forty patients (14.5 %) were identified with a pretherapeutic history of diabetes, and 20 (50 %) of them were treated with metformin (Adeberg et al 2015).…”
Section: Metformin Efficacy In Gbm: Clinical Evidencementioning
confidence: 99%
“…Two years later, Adeberg et al (2015) investigated the influence of diabetes mellitus, corticosteroid therapy and metformin therapy on progression and survival in primary GBM patients. Among 276 patients with primary GBM, forty patients (14.5 %) were identified with a pretherapeutic history of diabetes, and 20 (50 %) of them were treated with metformin (Adeberg et al 2015). Survival and correlations were assessed via t test and log-rank, univariate and multivariate Cox proportional hazards ratio analyses (Adeberg et al 2015).…”
Section: Metformin Efficacy In Gbm: Clinical Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, the energetic metabolism can bridge the above reported pathology with both metabolic effects and gut microbial activity. In fact, Adeberg et al reported that metformin is associated with prolonged progression-free survival in diabetic glioblastoma patients [71]. Notably, numerous experimental evidences link the metabolic effects of metformin with gut microbial modulation in both humans, where metformin increased the abundance in Escherichia spp.…”
Section: Brain and Mirsmentioning
confidence: 99%